Evaluating Pre-Electronic Certificate Readiness at the Langsa Land Office - Dwi Wulan Titik Andari; Arif Tri Wibowo; Nur Rahmanto; Dian Dewi Khasanah; Setiowati Setiowati (Jurnal Ilmu Hukum Kyadiren, 2026)
The transformation of electronic-based land services through the issuance of electronic certificates (Sert-el) requires the availability of accurate and reliable land data, particularly through the verification of Land Books (BT) and Measurement Letters (SU). Despite ongoing digitalization efforts, the implementation of Pre-Electronic Certificates (Pra-Sert-el) continues to face substantial challenges, especially regarding the integration of historical land records and the validation of supporting documents. This study aims to examine the implementation mechanism of Land Book verification in the transition toward Pra-Sert-el at the Langsa City Land Office, based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Number 3 of 2023. Using an empirical legal research method with a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The findings reveal that verification involves preparation, implementation, and quality control stages, although several technical, administrative, and institutional obstacles continue to impede effective implementation.